Evaluasi Hasil Belajar Peserta Didik Pada Lembaga Pendidikan - Ibrahim Ibrahim; Muhammad Arkan; Dea Patricia Yuke; Zulkipli Zulkipli (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This article discusses the evaluation of student learning outcomes in educational institutions. This type of research is a literature study with the characteristics that the research deals directly with text/scripts or numbers, the data is ready-to-use, library data is generally a secondary source and the process is not limited by space and time. The results obtained show that the evaluation of student learning outcomes in educational institutions is an important matter to be carried out and regulated in order to achieve the objectives of existing education. Implementation of the 2013 curriculum, must refer to the process and evaluation of learning outcomes according to existing guidelines. The problem that arises is that teachers feel that the new regulations regarding the assessment system are very complex, because they use a variety of different assessment tools to evaluate learning outcomes. Teacher competence must be increased and must be able to adjust to the implementation rules of the 2013 curriculum.